Thermodynamic Modelling of Gas Hydrate Formation in the Presence of Inhibitors and the Consideration of their Effect - Peyman Sabzi; Saheb Noroozi (ASEAN Journal of Chemical Engineering, 2014)
Gas hydrates formation is considered as one the greatest obstacles in gas transportation systems. Problems related to gas hydrate formation is more severe when dealing with transportation at low temperatures of deep water. In order to avoid formation of Gas hydrates, different inhibitors are used. Methanol is one of the most common and economically efficient inhibitor. Adding methanol to the flow lines, changes the thermodynamic equilibrium situation of the system. In order to predict these changes in thermodynamic behavior of the system, a series of modelings are performed using Matlab software in this paper. The main approach in this modeling is on the basis of Van der Waals & Plateau's thermodynamic approach. The obtained results of a system containing water, Methane and Methanol showed that hydrate formation pressure increases due to the increase of inhibitor amount in constant temperature and this increase is more in higher temperatures. Furthermore, these results were in harmony with the available empirical data.